2020
DOI: 10.3389/fpls.2020.00599
|View full text |Cite
|
Sign up to set email alerts
|

Drought Drives Spatial Variation in the Millet Root Microbiome

Abstract: Efforts to boost crop yield and meet global food demands while striving to reach sustainability goals are hindered by the increasingly severe impacts of abiotic stress, such as drought. One strategy for alleviating drought stress in crops is to utilize rootassociated bacteria, yet knowledge concerning the relationship between plant hosts and their microbiomes during drought remain under-studied. One broad pattern that has recently been reported in a variety of monocot and dicot species from both native and agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Library preparation and amplicon sequence data processing was performed according to Simmons et al (2018Simmons et al ( , 2020. To account for differences in sequencing read depth across samples, the data per sample were normalized by dividing its reads per ASV by the sum of usable reads, resulting in a table of relative abundance frequencies.…”
Section: Library Preparation and Amplicon Sequence Data Processingmentioning
confidence: 99%
“…Library preparation and amplicon sequence data processing was performed according to Simmons et al (2018Simmons et al ( , 2020. To account for differences in sequencing read depth across samples, the data per sample were normalized by dividing its reads per ASV by the sum of usable reads, resulting in a table of relative abundance frequencies.…”
Section: Library Preparation and Amplicon Sequence Data Processingmentioning
confidence: 99%
“…Drought stress not only perturbs the plant phenotype, but also the microbial community structure, leading to a decrease in the community diversity [13] , [48] , [49] , [50] . Interestingly, we witnessed opposite response patterns: the community diversity significantly decreased in the soil under drought treatment, but it did not differ or rather increased in the endosphere community.…”
Section: Discussionmentioning
confidence: 99%
“…16S amplicon sequencing reads were demultiplexed in QIIME2 (86) and then passed to DADA2 (87) to generate Amplicon Sequence Variants (ASVs), with taxonomies assigned using the August 2013 version of GreenGenes 16S rRNA gene database as described previously (16). All subsequent 16S statistical analyses were performed in R-v3.6.1 (88).…”
Section: Methodsmentioning
confidence: 99%
“…For example, enrichment of monoderm bacteria, such as Actinobacteria, during drought has been observed across diverse plant clades (6, 7, 13, 14). Notably, recent studies have demonstrated that plants mediate the shifts in bacterial communities during drought (15), and Actinobacterial enrichment during drought is dependent on signals produced by living roots (16). While monoderm bacteria are dominant during drought, their enrichment is transitory, with diderm bacteria reestablishing after rewatering (13).…”
Section: Introductionmentioning
confidence: 99%